2013
DOI: 10.1111/php.12110
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Structural Changes in Lung Tissue Infected by Paracoccidioides brasiliensis: FTIR Photoacoustic Spectroscopy and Histological Analysis

Abstract: This study evaluated physical, chemical and morphological changes in lungs of mice infected with Paracoccidioides brasiliensis. The animals were inoculated with 0.1 mL of fungal suspension of the P. brasiliensis 18 isolate and were euthanized 1, 2, 4 and 8 weeks after inoculation. The upper left lobe of the lung was isolated, fixed and processed for paraffin embedding. The sections were stained with H&E for histopathological study, with Gomori-Grocott to locate and identify the fungus, and with TUNEL immunosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…12 The interactions between microorganisms and loofa sponges can be analyzed by Fourier transform infrared-attenuated total reflectance (FTIR-ATR) spectrometry, because it allows evaluation of the physical/chemical structure of materials by detecting absorption bands from molecular chemical groups and the occurrence of their structural modifications. 12,20 In the present study, Agrobacterium sp. IFO 13140 cells were immobilized on a loofa sponge and subjected to five consecutive cycles for curdlan production, and the interaction between the cells and the matrix was determined.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…12 The interactions between microorganisms and loofa sponges can be analyzed by Fourier transform infrared-attenuated total reflectance (FTIR-ATR) spectrometry, because it allows evaluation of the physical/chemical structure of materials by detecting absorption bands from molecular chemical groups and the occurrence of their structural modifications. 12,20 In the present study, Agrobacterium sp. IFO 13140 cells were immobilized on a loofa sponge and subjected to five consecutive cycles for curdlan production, and the interaction between the cells and the matrix was determined.…”
Section: Introductionmentioning
confidence: 65%
“…Studies that have analyzed interactions between microorganisms and loofa sponges are still scarce . The interactions between microorganisms and loofa sponges can be analyzed by Fourier transform infrared‐attenuated total reflectance (FTIR‐ATR) spectrometry, because it allows evaluation of the physical/chemical structure of materials by detecting absorption bands from molecular chemical groups and the occurrence of their structural modifications …”
Section: Introductionmentioning
confidence: 99%
“…Pb can cause morphofunctional changes resulting from the invasion, adhesion and residence of the microorganism in the organs . In the lungs, PCM leads to the development of fibrosis, represented by the expressive expansion of the collagen fibers in the pulmonary parenchyma, a phenomenon that can evolve and lead a patient to develop respiratory insufficiency .…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies demonstrated their relevance in this area when used in modified arrangements, allowing coupling the methods with both optical biopsy or in situ optical fiber probes . These techniques can characterize the functional groups of organic compounds in tissues and enable a tissue in a physiological state to be distinguished from another in a pathological state . For this reason, they are powerful tools for the analysis of biological materials and may represent an alternative and advantageous procedure for diagnosis of infectious diseases, especially in experimental investigations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation